A simultaneous removal of ammonium and turbidity via an adsorptive coagulation for drinking water treatment process - Mohtar, S. S. (Springer, 2020)
The utilization of natural zeolite (NZ) as an adsorbent for NH4 + removal was investigated. Three types of NZ (i.e., NZ01, NZ02, and NZ03) were characterized, and their NH4 + adsorption process in aqueous solution was evaluated. The effect of pH towards NH4 + adsorption showed that the NZ01 has the highest NH4 + adsorption capacity compared with other natural zeolites used. The application of NZ01 for a simultaneous removal of NH4 + and turbidity in synthetic NH4 +-kaolin suspension by adsorptive coagulation process for treating drinking water was studied. The addition of NZ01 into the system increased the NH4 + removal efficiency (ηNH4+) from 11.64% without NZ01 to 41.86% with the addition of 0.2 g L−1 of NZ01. The turbidity removal (ηT), however, was insignificantly affected since the ηT was already higher than 98.0% over all studied parameter’s ranges. The thermodynamic and kinetic data analyses suggested that the removal of NH4+ obeyed the Temkin isotherm model and pseudo-second-order kinetic model, respectively. Generally, the turbidity removal was due to the flocculation of destabilized solid particles by alum in the suspension system. The ηNH4+ in surface water was 29.31%, which is lower compared with the removal in the synthetic NH4 +-kaolin suspension, but a high ηT (98.65%) was observed. It was found that the addition of the NZ01 could enhance the removal of NH4 + as well as other pollutants in the surface water.